2021
DOI: 10.1002/hep4.1684
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Up‐regulation of Biliary Fibrosis–Related Extracellular Matrix Molecules After Successful Portoenterostomy

Abstract: Successful portoenterostomy (SPE) improves the short-term outcome of patients with biliary atresia (BA) by relieving cholestasis and extending survival with native liver. Despite SPE, hepatic fibrosis progresses in most patients, leading to cirrhosis and a deterioration of liver function. The goal of this study was to characterize the effects of SPE on the BA liver transcriptome. We used messenger RNA sequencing to analyze global gene-expression patterns in liver biopsies obtained at the time of portoenterosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(98 reference statements)
0
4
1
Order By: Relevance
“…The association between SCTR and liver fibrosis was further strengthened by close correlations of SCTR with TGF-β and PDGF , growth factors known to mediate liver fibrosis 31 , 32 . However, unlike in previous experimental studies, SCTR associated with TGFB2 rather than TGFB1 , which is less abundantly expressed TGF-β isoform in BA 17 , 33 , 34 . Additional studies in cholestatic experimental animal models are needed to clarify whether the secretin/SCTR axis could be targeted to reduce fibrosis and biliary damage in BA 20 , 22 , 25 .…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The association between SCTR and liver fibrosis was further strengthened by close correlations of SCTR with TGF-β and PDGF , growth factors known to mediate liver fibrosis 31 , 32 . However, unlike in previous experimental studies, SCTR associated with TGFB2 rather than TGFB1 , which is less abundantly expressed TGF-β isoform in BA 17 , 33 , 34 . Additional studies in cholestatic experimental animal models are needed to clarify whether the secretin/SCTR axis could be targeted to reduce fibrosis and biliary damage in BA 20 , 22 , 25 .…”
Section: Discussioncontrasting
confidence: 91%
“…Herein, we have examined the prognostic and pathophysiological significance of 22 predetermined differentially expressed BA specific candidate genes 17 . Among them, SCTR showed unique associations with PE outcomes and liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular matrix (ECM) is critical for providing a niche for several cell types, such as intestinal stem cells [91] , and there is an increasing interest in exploring the role of ECM also for cholangiocytes in BA, as progressive fibrosis is frequently observed in BA patients. Pathway enrichment analysis of BA patients with low survival after KPE revealed that the top 10 most dysregulated pathways were ECM-related [92] and Kyrönlahti et al., (2021) observed an increase in ECM gene expression after KPE [93] . Furthermore, elevated expression of matrix metalloproteinase 7 (MMP7), which modulates ECM by breaking down for example fibronectin and proteoglycans, is seen in extrahepatic cholangiocytes in BA patients and serves as a biomarker for the disease (see below) [ 94 , 95 ].…”
Section: Novel Insights Into Biliary Atresia Pathomechanismsmentioning
confidence: 99%
“…IC is mostly found in pregnant women, accounting for 0.2-2% of all complications in pregnancies [3]. Long-term IC will progress to liver brosis and even cirrhosis, leading to a series of liver diseases such as primary biliary cirrhosis, primary sclerosing cholangitis, and biliary atresia [4,5]. At present, some drugs, such as rosiglitazone, obeticholic acid, and ursodeoxycholic acid (UDCA), are commonly used for IC treatment.…”
Section: Introductionmentioning
confidence: 99%